Frequency of Tension-type Headache in Females Presenting with Chronic Daily Headaches - Saleem, Taimoor; Khalid, Bassam; Naseer, Umer; Hussain, Mehmood; Khan, Hamna Ahmed; Nawaz, Khurram Haq (Pakistan Armed Forces Medical Journal, 2024)
Objective:  To assess the role of non-pharmacological interventions in relieving Tension-type headache.Study Design: Quasi experimental studyPlace and Duration of Study: Neurology department, Pak Emirates Military Hospital, Rawalpindi Pakistan, from Dec 2020 to May 2021.Methodology: Tension-Type Headache was diagnosed by physician using the International Classification of Headache Disorders III (ICHD-III). Patients were randomized into two groups, Group-A was intervention Group and Group-B was the control group. Both the groups were followed at 14 and 30 days. Visual analogue pain (VAP) scale and Headache Intensity Test 6 (HIT) was applied to evaluate the intensity of headache.Results:  Out of 600 patients with chronic daily headaches, 210(34%) patients had Tension-type headache. The mean age of these females was 35.4± 9.342 years. A total of 112(53%) were working, 172(81.9%) were married. In terms of level of education, 68(32.4%) had done matriculation, 29(13.8%) had done FSc.  and 113(53.8%) had completed higher education. At 28 days post intervention, there was significant improvement in Headache Impact Test (HIT) score (43.26±4.48 vs 49.81±5.52, p-value